2005
DOI: 10.1111/j.1600-6143.2005.01007.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Member of the CD20/FcεRIβ Family Overexpressed in Tolerated Allografts

Abstract: We identified a novel rat gene specifically overexpressed in tolerated heart allografts in a model of tolerance induced by donor-specific blood transfusion (DST). We named this gene TORID, for tolerancerelated and induced transcript. We show that TORID expression can be attributed to non-T cells infiltrating tolerated grafts. Interestingly, TORID overexpression was also observed in long-term grafts from a different model of tolerance in which chronic rejection does not occur. Comparison of the predicted amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
75
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(85 citation statements)
references
References 47 publications
8
75
2
Order By: Relevance
“…Because this molecule was preferentially expressed on resting macrophages and dendritic cells, we can only speculate as to its role in active tolerogenic pathways (23). Our observation demonstrating increased expression of this gene in blood of patients with acute rejection suggested that it was associated with alloantigen presentation and inflammation, suggesting that the tolerogenic potential of this molecule remains to be defined.…”
Section: The Physiological Expression Of This Oncoprotein Is Limited mentioning
confidence: 83%
See 1 more Smart Citation
“…Because this molecule was preferentially expressed on resting macrophages and dendritic cells, we can only speculate as to its role in active tolerogenic pathways (23). Our observation demonstrating increased expression of this gene in blood of patients with acute rejection suggested that it was associated with alloantigen presentation and inflammation, suggesting that the tolerogenic potential of this molecule remains to be defined.…”
Section: The Physiological Expression Of This Oncoprotein Is Limited mentioning
confidence: 83%
“…One of the genes analyzed, TMEM176B, originally described as TORID, was described as overexpressed in tolerated heart allografts in a model of tolerance induced by donorspecific blood transfusion with long-term survival without signs of chronic rejection (23). Because this molecule was preferentially expressed on resting macrophages and dendritic cells, we can only speculate as to its role in active tolerogenic pathways (23).…”
Section: The Physiological Expression Of This Oncoprotein Is Limited mentioning
confidence: 99%
“…Similar to TMEM176A, the level of human TMEM176B transcripts has been shown to be markedly elevated in transplanted livers that showed recurrence of HCV infection (Gehrau et al, 2011). On the other hand, the mRNA expression of rat Tmem176B (also known as rat TORID, or mouse Clast1/LR8) is highly correlated with tolerated allografts (transplanted tissue taken from a different individual of the same species) (Louvet et al, 2005; Condamine et al, 2010). This finding suggests that Tmem176B may be involved in the regulation of immune cell activation and tolerance (Louvet et al, 2005; Condamine et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the mRNA expression of rat Tmem176B (also known as rat TORID, or mouse Clast1/LR8) is highly correlated with tolerated allografts (transplanted tissue taken from a different individual of the same species) (Louvet et al, 2005; Condamine et al, 2010). This finding suggests that Tmem176B may be involved in the regulation of immune cell activation and tolerance (Louvet et al, 2005; Condamine et al, 2010). Indeed, the tissue mRNA expression profiles of rat and mouse Tmem176A or Tmem176B point to an important role in immune function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation